A unique internal ribosome entry site representing a dynamic equilibrium state of RNA tertiary structure in the 5′-UTR of Wheat yellow mosaic virus RNA1. Issue 1 (12th November 2019) - Geng, Guowei; Yu, Chengming; Li, Xiangdong; Yuan, Xuefeng
Abstract: Internal ribosome entry sites (IRESes) were first reported in RNA viruses and subsequently identified in cellular mRNAs. In this study, IRES activity of the 5′-UTR in Wheat yellow mosaic virus (WYMV) RNA1 was identified, and the 3′-UTR synergistically enhanced this IRES activity via long-distance RNA–RNA interaction between C 80 U 81 and A 7574 G 7575 . Within the 5′-UTR, the hairpin 1(H1), flexible hairpin 2 (H2) and linker region (LR1) between H1 and H2 played an essential role in cap-independent translation, which is associated with the structural stability of H1, length of discontinuous stems and nucleotide specificity of the H2 upper loop and the long-distance RNA–RNA interaction sites in LR1. The H2 upper loop is a target region of the eIF4E. Cytosines (C 55, C 66, C 105 and C 108 ) in H1 and H2 and guanines (G 73, G 79 and G 85 ) in LR1 form discontinuous and alternative base pairing to maintain the dynamic equilibrium state, which is used to elaborately regulate translation at a suitable level. The WYMV RNA1 5′-UTR contains a novel IRES, which is different from reported IRESes because of the dynamic equilibrium state. It is also suggested that robustness not at the maximum level of translation is the selection target during evolution of WYMV RNA1.